Beneficial effects of novel aureobasidium pullulans strains produced beta-1,3-1,6 glucans on interleukin-6 and D-dimer levels in COVID-19 patients; results of a randomized multiple-arm pilot clinical study - Raghavan, Kadalraja; Dedeepiya, Vidyasagar Devaprasad; Suryaprakash, Vaddi; Rao, Kosagi-Sharaf; Ikewaki, Nobunao; Sonoda, Tohru; Levy, Gary A.; Iwasaki, Masaru; Senthilkumar, Rajappa; Preethy, Senthilkumar; Abraham, Samuel JK (Biomedicine & pharmacotherapy, 2022)
In this pilot clinical study, we report the beneficial effects of beta glucans derived from two strains AFO-202 and N-163 of a black yeast Aureobasidium pullulans on the biomarkers for cytokine storm and coagulopathy in COVID-19 patients. A total of 24 RT-PCR positive COVID-19 patients were recruited and randomly divided into three groups (Gr): Gr. 1 control (n = 8) – Standard treatment; Gr. 2: Standard treatment + AFO-202 beta glucan (n = 8); and Gr. 3, Standard treatment + combination of AFO-202 and N-163 beta glucans (n = 8) for 30 days. There was no mortality or requirement of ventilation of the subjects in any of the groups. There was a decrease in D-Dimer values (751 ng/ml to 143.89 ng/ml) and IL-6 values (7.395–3.16 pg/ml) in Gr. 1 in 15 days but the levels increased to abnormal levels on day 30 (D-Dimer: 202.5 ng/ml; IL-6 55.37 pg/ml); which steadily decreased up to day 30 in groups 2 (D-dimer: 560.99 ng/dl to 79.615; IL-6: 26.18–3.41 pg/ml) and 3 (D-dimer: 1614 ng/dl to 164.25 ng/dl; IL-6: 6.25–0.5 pg/ml). The same trend was observed with ESR. LCR and LeCR increased while NLR decreased significantly in Gr. 3. CD4 + and CD8 + T cell count showed relatively higher increase in Gr.3. There was no difference in CRP within the groups. As these beta glucans are well known food supplements with a track record for safety, larger multi-centric clinical studies are recommended to validate their use as an adjunct in the management of COVID-19 and the ensuing long COVID-19 syndrome. [Display omitted] •Multiple-arm clinical trial of beta 1,3-1,6 glucans in COVID-19 patients.•Control arm could maintain IL-6 and D-DIMER levels only till day-15.•AFO-202 beta glucan consumption yielded IL-6 and D-DIMER control up to day-30.•N-163 +AFO-202 maintained NLR, LCR, LeCR with IL-6 and D-DIMER levels up to day-30.•CD4 + and CD8 + T cell levels were shown advantageous in N-163 +AFO-202 group.